Trade Openness and Unemployment: A Panel Cointegration for the G20 Countries - Zahrah, Zahrah; Hendri, Wira; Febriana, Widia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
In 1999, G20 was formed to provide a new mechanism for extending the key economic and financial policy issue and promote co-operation for gaining stable and sustainable world economic growth. The world trading system creates a new founded trade and investment working group which impact on the high productions due to the trade openness through the high job opportunities. However, there is different effects founded between trade openness and unemployment among G20 countries. A notable research gap in this study is the absence of congruence between the results of previous studies and the phenomena observed in the field, particularly in the context of a more extensive population sample, specifically the G20 countries. It urges a further examination trade openness and unemployment in order to gain a comprehensive understanding of the current state of affairs. It used the data spanning over 25 years (1999 – 2023) in G20 Countries for unemployment, trade openness, GDP, Government Expenditure in Education, Trade and Investment Freedom. The analysis of model used Panel Unit Root Test, Panel Cointegration Test as well as FMOLS and DOLS estimator. The result shows that all variables are cointegrated for the entire G20 countries in long-run relationship. However, the GDP has significant and negative effect on unemployment rate but GEE has positive relationship even it has significant effect towards unemployment rate. While trade and investment freedom have negative and unsignificant effect on unemployment rate, whereas the trade openness has a positive nexus with unemployment rate.